Do all vegetarians have a lower cardiovascular risk? A prospective study. Issue 3 (March 2023) - Petermann-Rocha, Fanny; Celis-Morales, Carlos; Pell, Jill P.; Ho, Frederick K.
Summary: Background: Vegetarian diets are heterogeneous and their health benefits may vary. This study aimed to compare the cardiovascular risk among vegetarian diets that meet existing health guidelines, those that do not, and diets that include red meat. Methods: 391, 124 participants (55.5% women) from the UK Biobank prospective population-based study were included. Using data from a food frequency questionnaire, participants were categorised into lacto-vegetarian or meat-eaters. Then, both groups were dichotomised into a healthier and less healthy group using an unweighted score based on current UK guidelines. Ischaemic heart disease (IHD) and myocardial infarction (MI) incidence – both separately and as a composite of major adverse cardiovascular events (MACE) – were the outcomes included. Associations between types of diets and health outcomes were investigated using Cox proportional hazard models adjusted for confounder factors. Results: After a median follow-up of 10.4 years, there were 40, 048 MACE. When the analyses were adjusted for prevalent morbidity and lifestyle factors, people who followed healthier vegetarian and meat-eater diets had 18% (95% CI: 0.73 to 0.92) and 5% (95% CI: 0.93 to 0.97) lower risk of MACE than less healthy meat-eaters. Similar patterns were identified for the individual outcomes, with the strongest association observed for MI. The cardiovaculasr risk among less healthy vegetarians and less healthy meat-eaters were not significnatly different. Conclusions: Vegetarian diets are heterogeneous and the cardiovascular risk varied accordingly. Future studies should consider the overall dietary patterns of vegetarians rather than just based on meat consumption. Guidelines advocating a plant-based diet need to stress the importance of overall diet quality in addition to the reduction of meat.